2013
DOI: 10.1038/npp.2013.327
|View full text |Cite
|
Sign up to set email alerts
|

Stress-System Genes and Life Stress Predict Cortisol Levels and Amygdala and Hippocampal Volumes in Children

Abstract: Depression has been linked to increased cortisol reactivity and differences in limbic brain volumes, yet the mechanisms underlying these alterations are unclear. One main hypothesis is that stress causes these effects. This is supported by animal studies showing that chronic stress or glucocorticoid administration can lead to alterations in hippocampal and amygdala structures. Relatedly, life stress is cited as one of the major risk factors for depression and candidate gene studies have related variation in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(222 citation statements)
references
References 45 publications
10
207
0
2
Order By: Relevance
“…Klengel et al (2013) demonstrated that this G × E is associated with increased risk for stress-related disorders including PTSD and depression. In addition, FKBP5 risk variants have been associated with neuroimaging markers implicated in stress-related disorders, including amygdala and hippocampal volume and reactivity (Fani et al, 2013;Holz et al, 2015;Pagliaccio et al, 2014;White et al, 2012). Several important features of this story are worth highlighting.…”
Section: Gene-environment Interactionmentioning
confidence: 99%
“…Klengel et al (2013) demonstrated that this G × E is associated with increased risk for stress-related disorders including PTSD and depression. In addition, FKBP5 risk variants have been associated with neuroimaging markers implicated in stress-related disorders, including amygdala and hippocampal volume and reactivity (Fani et al, 2013;Holz et al, 2015;Pagliaccio et al, 2014;White et al, 2012). Several important features of this story are worth highlighting.…”
Section: Gene-environment Interactionmentioning
confidence: 99%
“…Larger-scale longitudinal studies of multiple variables are among promising examples (e.g. Waters et al [44], and Washington University investigators [64 ]). The stressdepression field is in the early phases of an exhilarating era of creative integration.…”
Section: Integrative Perspectivesmentioning
confidence: 99%
“…Conversely, two studies described a protective effect of the presence of TAT copies against depression in individuals with a history of abuse [17,19]. Many factors could explain these discrepancies, such as different types of traumatic events and age of exposure, variability in the severity and comorbidity of mental disorders, interference of other variables such as aminergic systems and possible associations between CRHR1 SNPs and SNPs of other genes [59,60].…”
Section: Research Marcos Gonçalves De Rezendementioning
confidence: 99%